BIOKONVERSI SERBUK GERGAJI KAYU HUTAN TANAMAN SEBAGAI MEDIA JAMUR PANGAN Pleurotus spp. - Djarwanto; Sihati Suprapti; Agus Ismanto (BRIN Publishing, 2016)
Pleurotus spp. for food has been cultivated on various lignocellulose wastes. This paper studies the feasibility of fast grown wood species sawdust waste as medium for the cultivation of edible mushroom, Pleurotus spp. Wood species studied were mangium (Acacia mangium), damar (Agathis borneonensis) and rubberwood (Hevea brasiliensis). Twenty percent rice bran, 1% CaCO₃; 1% gypsum; 0.1%, 0.3% and 0.5% urea fertilizer as well as TSP (tri-superphosphate); and distilled water, were added to each wood sawdust formula. The results showed that sawdust from those three wood species could indicatively be utilized as medium for cultivating Pleurotus spp. Supplementation of urea into the media performed better result than that of TSP. The highest Biological Conversion Efficiency (BCE) value was obtained on rubberwood containing 0.3% fertilizer. With respect to the mushroom species in their ability to convert wood sawdust into mushroom biomass, the highest BCE value was recorded from Pleurotus ostreatus, then P. flabellatus, while P. sajor-caju was recorded as the lowest. Inoculation of Pleurotus mushroom at rubber-wood sawdust decreased the C/N ratio, although the used-medium was un-ripe compost.